Recommendations about feeding systems - Ruíz, M.; Wilcox, C.J.; Pezo, Danilo A.; Taylor, R.; Chaves, C.; Rosero, O. (Inter-American Institute for Cooperation on Agriculture, 1992)
Discussion on recommendations about feeding systems, w. ref. to the growing and finishing trials; the nutrition-reproduction interphase; dairy cattle; additional statistical topics; and the research priorities.